A method that can simultaneously promote H 2 O 2 Electrosynthesis and Fe 2+ Regenerated hydrophobic cathode material and preparation method and application thereof

By modifying the octavinyl-POSS derivative on the surface of activated carbon fibers, a hydrophobic composite cathode material was prepared, which solved the problems of low electrosynthesis efficiency of H2O2 and slow Fe2+ regeneration rate in electrofenton technology, and achieved efficient removal of new organic pollutants.

CN115537849BActive Publication Date: 2025-04-22ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211220147.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-08
Publication Date
2025-04-22
Estimated Expiration
2042-10-08

AI Technical Summary

Technical Problem

Electrofenton technology has problems with low H2O2 electrosynthesis efficiency and slow Fe2+ regeneration rate when dealing with new organic pollutants.

Method used

By modifying the octavinyl-POSS derivative on the surface of activated carbon fibers, a hydrophobic composite cathode material is prepared, which can accelerate oxygen mass transfer and promote the electrical regeneration of Fe2+.

Benefits of technology

The composite cathode material significantly improves the electrosynthesis yield of H2O2 under no aeration conditions, accelerates the regeneration of Fe2+, and improves the removal efficiency of new organic pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115537849B_ABST
    Figure CN115537849B_ABST
Patent Text Reader

Abstract

The invention discloses a method for simultaneously promoting H2O2 electrosynthesis and Fe 2+ Regenerated hydrophobic cathode material and preparation method and application thereof. The present invention uses octavinyl-POSS, tetrahydrofuran and activated carbon fiber as raw materials, dissolves the octavinyl-POSS in a tetrahydrofuran solution, applies the mixed solution dropwise to the surface of the activated carbon fiber, and then calcines at high temperature to obtain an activated carbon fiber composite cathode modified with an octavinyl-POSS derivative. The cathode material of the present invention can be used as the cathode of a homogeneous electro-Fenton system. The composite cathode has hydrophobicity and a large specific surface area, can accelerate the mass transfer and diffusion of oxygen on the cathode surface, and greatly improves the electrogenerated H2O2 yield in the absence of aeration; at the same time, the octavinyl-POSS derivative is easy to adsorb iron ions in the electro-Fenton system and accelerate the electroreduction of Fe 3+ Regenerated Fe 2+ process, increasing the production of hydroxyl radicals, thereby achieving efficient removal of new organic pollutants in water bodies, and can be reused many times, which has good application prospects in the field of electrochemical water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental functional materials and electrochemical water treatment, and specifically relates to a method for simultaneously promoting H 2 O 2 Electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material and the application of the electrode in an electro-Fenton system. Background Art

[0002] With the deepening of urban industrialization and the development of the chemical industry, more and more new organic pollutants (EOCs) are frequently detected in water bodies. EOCs have complex components, poor biodegradability, and are often biotoxic, environmentally persistent, and bioaccumulative. Even at low concentrations in the water environment, long-term exposure may accumulate in organisms and gradually enrich along the food chain, thereby posing potential hazards to environmental organisms and human health.

[0003] Advanced oxidation technology is considered an important means to treat the above-mentioned new organic pollutants. Among them, electro-Fenton technology, as a green and environmentally friendly advanced oxidation technology, is highly favored in the field of electrochemical water treatment. This technology can generate H 2 O 2 It reacts with the added ferrous ions to produce hydroxyl radicals (•OH) with strong oxidizing ability, thereby achieving efficient removal of new organic pollutants in water. However, electro-Fenton technology still has 2e - Oxygen reduction reaction produces H 2 O 2 Low efficiency and Fe 2+ The core problem is the slow regeneration rate. 2 The solubility in water is low, and the cathode 2 electron oxygen reduction reaction (2e - -ORR) 2 O 2 The process is limited to O 2 Mass transfer control, resulting in a slow 2e - -ORR kinetics and low H 2 O 2 Hydrophobic gas diffusion electrode is currently the most widely used strategy to improve oxygen mass transfer efficiency. By improving the hydrophobicity of the cathode material, it can effectively promote the transmission and enrichment of oxygen from the outside to the cathode surface without dissolving it in the electrolyte, thereby increasing H 2 O 2 At the same time, increasing the adsorption of iron ions on the cathode surface can effectively promote Fe 2+ Based on this, the present invention proposes a method that can simultaneously promote H 2 O 2 Electrosynthesis and Fe 2+Preparation method of regenerated hydrophobic cathode material and its application in electro-Fenton degradation of new organic pollutants. Summary of the invention

[0004] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a method for promoting H 2 O 2 Electrosynthesis and Fe 2+ Regenerated hydrophobic cathode material and preparation method and application thereof.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] In a first aspect, the present invention provides a method for simultaneously promoting H 2 O 2 Electrosynthesis and Fe 2+ The preparation method of the regenerated hydrophobic cathode material specifically comprises the following steps:

[0007] (1) The activated carbon fiber is ultrasonically cleaned with anhydrous ethanol and deionized water in sequence, and dried for later use;

[0008] (2) dissolving octavinyl-POSS in an organic solvent by ultrasonic treatment to prepare an octavinyl-POSS solution;

[0009] (3) applying the octavinyl-POSS solution obtained in step (2) dropwise onto one side surface of the activated carbon fiber pretreated in step (1), and allowing to stand in a fume hood until the organic solvent evaporates, and then drying in a vacuum drying oven;

[0010] (4) Place the material obtained in step (3) in a tube furnace at N 2 The activated carbon fiber composite cathode modified with octavinyl-POSS derivative was obtained by calcination under atmospheric conditions, which was recorded as POSS / ACF.

[0011] Furthermore, in step (2), the organic solvent is tetrahydrofuran.

[0012] Furthermore, in step (2), the concentration of octavinyl-POSS in the organic solvent is 1.25-12.5 mg / mL, preferably 2.5-3 mg / mL.

[0013] Furthermore, in step (3), the drop coating amount of octavinyl-POSS on one side of the activated carbon fiber is 0.625-6.25 mg / cm 2 , preferably 0.625~3.125mg / cm 2 The specific surface area of ​​POSS / ACF obtained in step (4) is 880m 2 / g or above.

[0014] Furthermore, in step (3), the standing time in the fume hood is 15-60 min, preferably 30 min; the vacuum drying temperature is 50-80°C, and the vacuum drying time is 2-5 h, preferably 3 h.

[0015] Furthermore, the calcination conditions in the tubular furnace in step (4) are: heating from room temperature to 200-500°C, preferably to 350°C, then calcining at a constant temperature for 5-60 min, preferably 30 min, and finally cooling to room temperature; the heating rate is 2-10°C / min, preferably 5°C / min.

[0016] In a second aspect, the present invention provides an application of a hydrophobic cathode material prepared by the above method in preparing hydrogen peroxide in an electro-Fenton system.

[0017] Furthermore, in situ electrosynthesis of H 2 O 2 The application process comprises: using an electrolytic cell without a diaphragm in the middle as a reactor, using a 0.01-0.1 mol / L sodium sulfate aqueous solution as an electrolyte at room temperature, adjusting the pH of the electrolyte to 2-4, using the hydrophobic cathode material as the system cathode, using a platinum electrode as the system anode, and continuously stirring the electrolyte at a rotation speed of 1000-3000 r / min to prepare hydrogen peroxide; the cathode and the anode are externally connected to a DC power supply, and the cathode is applied with a potential of 5-40 V.

[0018] In a third aspect, the present invention also provides an application of the above-mentioned hydrophobic cathode material in degrading new organic pollutants in an electro-Fenton system.

[0019] Furthermore, the application process of degrading new organic pollutants in water bodies includes: using an electrolytic cell without a diaphragm in the middle as a reactor, at room temperature, using an aqueous solution containing 0.01-0.1 mol / L sodium sulfate, 0.1-1 mM ferrous sulfate and 10-50 mg / L organic pollutants as an electrolyte, adjusting the pH of the electrolyte to 2-4, using the hydrophobic cathode material as the cathode and the platinum sheet as the anode to construct the homogeneous electro-Fenton system, continuously stirring the electrolyte at a speed of 1000-3000 r / min to degrade new organic pollutants; the cathode and the anode are externally connected to a DC power supply, and the potential applied to the cathode is 5-40 V; the new organic pollutant is one of bisphenol A, carbamazepine, and chloroquine.

[0020] The composite cathode of the present invention has hydrophobicity and a large specific surface area, which can accelerate the mass transfer and diffusion of oxygen on the cathode surface, and greatly improve the electrogenerated H in the absence of aeration. 2 O 2 Yield; At the same time, the octavinyl-POSS derivative easily adsorbs iron ions in the electro-Fenton system and accelerates the electroreduction of Fe 3+ Regenerated Fe2+ process, increasing the production of hydroxyl radicals, thereby achieving efficient removal of new organic pollutants in water.

[0021] Compared with the prior art, the present invention has the following excellent effects:

[0022] 1. The preparation method of the composite cathode of the present invention is simple. The present invention selects octavinyl-POSS with a hydrophobic porous structure, and synthesizes an activated carbon fiber composite cathode modified with an octavinyl-POSS derivative by drop coating and one-step calcination. In addition, the activated carbon fiber used in the present invention has a large specific surface area (900m 2 / g), strong conductivity, and many electrochemical active sites, which are beneficial to improving the electrocatalytic degradation performance of the composite cathode.

[0023] 2. Electrogenerated H using the composite cathode of the present invention 2 O 2 The composite cathode of the present invention can efficiently generate H without aeration. 2 O 2 Compared with the unmodified activated carbon fiber electrode, the hydrogen peroxide yield increased by 86% after 2 h of reaction.

[0024] 3. Fe used in the composite cathode of the present invention 2+ The regeneration rate is fast. The composite cathode of the present invention is used in a homogeneous electro-Fenton system, which can effectively promote the 2+ Compared with the unmodified activated carbon fiber electrode, the Fe 2+ / Fe 3+ The ratio increased by 85%, and the removal rate of new organic pollutants increased by 64%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The contact angle test comparison diagram of Example 1 (a) and Comparative Example 1 (b) is shown.

[0026] Figure 2 This is a graph comparing the yields of hydrogen peroxide synthesized by electrocatalysis using the hydrophobic composite cathodes (POSS / ACF) of Example 1, Example 2, Example 3, and Example 4 and the ACF of Comparative Example 1.

[0027] Figure 3 The graph shows the degradation effect of bisphenol A on the electrode materials of Example 1 and Comparative Example 1 under the electro-Fenton system.

[0028] Figure 4 The diagram shows the mineralization effect of the electrode materials of Example 1 and Comparative Example 1 on bisphenol A under the electro-Fenton system.

[0029] Figure 5The graph is a graph showing the change in iron ion concentration of the electrode materials of Example 1 and Comparative Example 1 in the electro-Fenton system.

[0030] Figure 6 This is a diagram showing the mineralization effect of the electrode material of Example 1 on different new organic pollutants in an electro-Fenton system. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0032] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. The activated carbon fiber in the examples of the present invention is made by burning viscose fiber, with a carbon content of more than 95%, and is purchased from Jiangsu Sutong Carbon Fiber Co., Ltd.

[0033] Embodiment 1:

[0034] A method that can simultaneously promote H 2 O 2 Electrosynthesis and Fe 2+ The preparation of the regenerated hydrophobic cathode material is as follows:

[0035] (1) The activated carbon fibers (2*2*0.2 cm) were ultrasonically cleaned with anhydrous ethanol and deionized water for 3 times, 10 min each time, to remove impurities such as grease, and then dried in a vacuum drying oven at 60 °C for 6 h to obtain pretreated activated carbon fibers (about 0.25 g).

[0036] (2) 5 mg of octavinyl-POSS (the mass of octavinyl-POSS is 2 wt.% of the mass of activated carbon fibers) was dissolved in 2 mL of tetrahydrofuran by ultrasonic treatment to obtain a tetrahydrofuran solution containing octavinyl-POSS.

[0037] (3) The solution obtained in step (2) is dripped onto one side surface of the activated carbon fiber pretreated in step (1), and allowed to stand in a fume hood for 30 min; after the tetrahydrofuran evaporates, the material is placed in a vacuum drying oven at 60° C. and dried for 3 h.

[0038] (4) The material obtained in step (3) was placed in a tube furnace and heated from room temperature to 350°C at a heating rate of 5°C / min, and then heated under N 2 The temperature was kept constant in the atmosphere for 30 min, and after cooling to room temperature, an activated carbon fiber composite cathode modified with an octavinyl-POSS derivative was obtained, which was recorded as 2wt.%POSS / ACF.

[0039] The 2wt.% POSS / ACF sample obtained in Example 1 was tested for water contact angle. Figure 1As shown in the sub-figure (a), the water contact angle of 2wt.% POSS / ACF is 135°, and the surface is hydrophobic.

[0040] Example 2

[0041] A method that can simultaneously promote H 2 O 2 Electrosynthesis and Fe 2+ The preparation of the regenerated hydrophobic cathode material is as follows:

[0042] (1) The activated carbon fibers (2*2*0.2 cm) were ultrasonically cleaned with anhydrous ethanol and deionized water for 3 times, 10 min each time, to remove impurities such as grease, and then dried in a vacuum drying oven at 60 °C for 6 h to obtain pretreated activated carbon fibers (about 0.25 g).

[0043] (2) By ultrasonic treatment, 2.5 mg of octavinyl-POSS (the mass of octavinyl-POSS is 1 wt.% of the mass of activated carbon fiber) was dissolved in 2 mL of tetrahydrofuran to obtain a tetrahydrofuran solution containing octavinyl-POSS.

[0044] (3) The solution obtained in step (2) is dripped onto one side surface of the activated carbon fiber pretreated in step (1), and allowed to stand in a fume hood for 30 min; after the tetrahydrofuran evaporates, the material is placed in a vacuum drying oven at 60° C. and dried for 3 h.

[0045] (4) The material obtained in step (3) was placed in a tube furnace and heated from room temperature to 350°C at a heating rate of 5°C / min, and then heated under N 2 The temperature was kept constant in the atmosphere for 30 min, and after cooling to room temperature, an activated carbon fiber composite cathode modified with an octavinyl-POSS derivative was obtained, which was recorded as 1wt.%POSS / ACF.

[0046] Example 3

[0047] A method that can simultaneously promote H 2 O 2 Electrosynthesis and Fe 2+ The preparation of the regenerated hydrophobic cathode material is as follows:

[0048] (1) The activated carbon fibers (2*2*0.2 cm) were ultrasonically cleaned with anhydrous ethanol and deionized water for 3 times, 10 min each time, to remove impurities such as grease, and then dried in a vacuum drying oven at 60 °C for 6 h to obtain pretreated activated carbon fibers (about 0.25 g).

[0049] (2) 12.5 mg of octavinyl-POSS (the mass of octavinyl-POSS is 5 wt.% of the mass of the activated carbon fiber) was dissolved in 2 mL of tetrahydrofuran by ultrasonic treatment to obtain a tetrahydrofuran solution containing octavinyl-POSS.

[0050] (3) The solution obtained in step (2) is dripped onto one side surface of the activated carbon fiber pretreated in step (1), and allowed to stand in a fume hood for 30 min; after the tetrahydrofuran evaporates, the material is placed in a vacuum drying oven at 60° C. and dried for 3 h.

[0051] (4) The material obtained in step (3) was placed in a tube furnace and heated from room temperature to 350°C at a heating rate of 5°C / min, and then heated under N 2 The temperature was kept constant in the atmosphere for 30 min, and after cooling to room temperature, an activated carbon fiber composite cathode modified with an octavinyl-POSS derivative was obtained, which was recorded as 5wt.%POSS / ACF.

[0052] Example 4

[0053] A method that can simultaneously promote H 2 O 2 Electrosynthesis and Fe 2+ The preparation of the regenerated hydrophobic cathode material is as follows:

[0054] (1) The activated carbon fibers (2*2*0.2 cm) were ultrasonically cleaned with anhydrous ethanol and deionized water for 3 times, 10 min each time, to remove impurities such as grease, and then dried in a vacuum drying oven at 60 °C for 6 h to obtain pretreated activated carbon fibers (about 0.25 g).

[0055] (2) 25 mg of octavinyl-POSS (the mass of octavinyl-POSS is 10 wt.% of the mass of activated carbon fibers) was dissolved in 2 mL of tetrahydrofuran by ultrasonic treatment to obtain a tetrahydrofuran solution containing octavinyl-POSS.

[0056] (3) The solution obtained in step (2) is dripped onto one side surface of the activated carbon fiber pretreated in step (1), and allowed to stand in a fume hood for 30 min; after the tetrahydrofuran evaporates, the material is placed in a vacuum drying oven at 60° C. and dried for 3 h.

[0057] (4) The material obtained in step (3) was placed in a tube furnace and heated from room temperature to 350°C at a heating rate of 5°C / min, and then heated under N 2 The temperature was kept constant in the atmosphere for 30 min, and after cooling to room temperature, an activated carbon fiber composite cathode modified with an octavinyl-POSS derivative was obtained, which was recorded as 10wt.%POSS / ACF.

[0058] Comparative Example 1:

[0059] An activated carbon fiber cathode of an unmodified octavinyl-POSS derivative is prepared by the following specific steps:

[0060] (1) The activated carbon fibers (2*2*0.2 cm) were ultrasonically cleaned with anhydrous ethanol and deionized water for 3 times, 10 min each time, to remove impurities such as grease, and then dried in a vacuum drying oven at 60 °C for 6 h to obtain pretreated activated carbon fibers (about 0.25 g).

[0061] (2) The material obtained in step (1) was placed in a tube furnace and heated from room temperature to 350°C at a heating rate of 5°C / min, and then heated under N 2 The temperature was kept constant in the atmosphere for 30 min, and after cooling to room temperature, an unmodified activated carbon fiber cathode was obtained, which was recorded as ACF.

[0062] The ACF sample obtained in Example 1 was tested for water contact angle. Figure 1 As shown in the sub-figure (b), the water contact angle of ACF is 0° and the surface is hydrophilic.

[0063] The specific surface areas of the materials finally obtained in Examples 1 to 4 and Comparative Example 1 are shown in Table 1:

[0064]

[0065] Application Example 1

[0066] The hydrophobic composite cathode (POSS / ACF) prepared in Examples 1-4 and the ACF prepared in Comparative Example 1 were subjected to an electrocatalytic hydrogen peroxide production test, and the specific steps were as follows:

[0067] All reactions were carried out at room temperature of 25°C, with an external DC power supply of 20 V, a multimeter to observe the current, and a magnetic rotor to stir at a speed of 2500 r / min. The determination of hydrogen peroxide was carried out using the potassium titanium oxalate method. In a 250 mL electrolytic cell, 200 mL of 0.05 mol / L sodium sulfate solution was used as the electrolyte (1 mol / L sulfuric acid solution was added to adjust the initial pH of the system to 3), the prepared electrode material was used as the system cathode, and the platinum electrode (2.5 cm×3 cm) was used as the anode. Electrochemical experiments were carried out without adding ferrous ions. Water samples were extracted at certain time intervals to determine the concentration of hydrogen peroxide.

[0068] Figure 2 The graph is a comparison of the yield of hydrogen peroxide synthesized by electrocatalysis using the hydrophobic composite cathodes (POSS / ACF) of Example 1, Example 2, Example 3, and Example 4 and the ACF of Comparative Example 1. Figure 2It can be seen that the H 2 O 2 The generation rate is significantly faster than that of the system with ACF as the cathode. After 2 h of reaction, the H in the 2wt.% POSS / ACF prepared in Example 1, the 1wt.% POSS / ACF prepared in Example 2, the 5wt.% POSS / ACF prepared in Example 3, the 10wt.% POSS / ACF prepared in Example 4 and the ACF system prepared in Comparative Example 1 is 1.34 W / m. 2 O 2 The yields were 10.44 mg / L, 9.78 mg / L, 8.74 mg / L, 8.21 mg / L and 5.66 mg / L, respectively. 2 O 2 The electrosynthetic performance was affected by the amount of POSS modification, where 2wt.% POSS / ACF hydrophobic cathode electrocatalyzed the generation of H 2 O 2 Highest yield.

[0069] Application Example 2

[0070] The hydrophobic composite cathode (2 wt.% POSS / ACF) prepared in Example 1 and the ACF prepared in Comparative Example 1 were subjected to an electro-Fenton degradation test of bisphenol A, and the specific steps were as follows:

[0071] The electro-Fenton degradation experiment of bisphenol A was carried out in a 250 mL electrolytic cell. The treatment object was 200 mL of bisphenol A simulated wastewater (containing 0.05 mol / L sodium sulfate and 20 mg / L bisphenol A). During the reaction, the reaction temperature was controlled at 25°C using a low-temperature thermostatic bath. The 2wt.% POSS / ACF prepared in Example 1 or the ACF prepared in Comparative Example 1 was used as an electro-Fenton cathode, and a platinum electrode (2.5 cm×3 cm) was used as an anode, with a distance of 2 cm between the cathode and the anode; ferrous sulfate heptahydrate was used as a ferrous ion source, and its concentration in the electrolyte was 0.5 mM; 1 mol / L sulfuric acid solution was added dropwise to adjust the initial pH of the system to 3, an external DC power supply was connected, and the current was observed using a multimeter. The wastewater was subjected to a constant potential degradation experiment for 6 h at a voltage of 20 V. During the experiment, a magnetic rotor was used to continuously stir the electrolyte (speed 2500 r / min), and water samples were extracted at certain time intervals, and the bisphenol A concentration, TOC concentration, total iron ion concentration and Fe in the system were measured using Agilent liquid chromatography, total organic carbon (TOC) analyzer, atomic absorption spectrometry and o-phenanthroline method. 2+ The changes of indicators such as ion concentration are detected.

[0072] Figure 3 and Figure 4The figure shows the degradation effect and mineralization effect of the electrode materials of Example 1 and Comparative Example 1 on bisphenol A under the electro-Fenton system. As shown in the figure, the ACF electrode prepared in Comparative Example 1 has a removal rate of about 72% for bisphenol A within 30 minutes of reaction, while its mineralization rate for bisphenol A within 6 hours of reaction is only 52%. In comparison, the 2wt.% POSS / ACF electrode prepared in Example 1 removes 90% of bisphenol A within 30 minutes, and the mineralization rate reaches 81% at 6 hours. This result shows that the hydrophobic composite cathode made of octavinyl-POSS introduced into the activated carbon fiber can greatly improve the ability of the cathode to degrade bisphenol A by electro-Fenton.

[0073] Figure 5 The graph of the change of iron ion concentration of the electrode materials of Example 1 and Comparative Example 1 in the electro-Fenton system. As shown in the figure, the total iron ions and Fe in the system solution of the ACF electrode prepared in Comparative Example 1 within 2 h of reaction are 2+ The concentrations were 0.361 mM and 0.028 mM, respectively. In comparison, the 2 wt.% POSS / ACF electrode prepared in Example 1 had a decrease in total iron ions and Fe 2+ The concentrations were 0.326 mM and 0.118 mM, respectively. The results showed that the modification of POSS derivatives can effectively promote the enrichment of iron ions on the cathode surface and Fe 2+ Electrical regeneration process.

[0074] in addition Figure 5 It can also be seen that the total iron concentration in Comparative Example 1 is slightly higher than that in the present invention, further demonstrating that the POSS loading enhances the adsorption of iron ions.

[0075] Application Example 3

[0076] The hydrophobic composite cathode (2wt.% POSS / ACF) prepared in Example 1 was subjected to an electro-Fenton degradation test of new organic pollutants such as bisphenol A, carbamazepine, and chloroquine. The specific steps are as follows:

[0077] The experiment of electro-Fenton degradation of new organic pollutants was carried out in a 250 mL electrolytic cell, and the treatment object was 200 mL of simulated wastewater of new organic pollutants (containing 0.05 mol / L sodium sulfate and 20 mg / L of new organic pollutants). During the reaction, the reaction temperature was controlled at 25°C using a low-temperature thermostat. The 2wt.% POSS / ACF prepared in Example 1 was used as the electro-Fenton cathode, and the platinum electrode (2.5 cm×3 cm) was used as the anode, with a distance of 2 cm between the cathode and the anode; ferrous sulfate heptahydrate was used as the ferrous ion source, and its concentration in the electrolyte was 0.5 mM; 1 mol / L sulfuric acid solution was added dropwise to adjust the initial pH of the system to 3, an external DC power supply was connected, and the current was observed using a multimeter. The wastewater was subjected to a constant potential degradation experiment at a voltage of 20 V for 6 h. During the experiment, the electrolyte was continuously stirred using a magnetic rotor, and water samples were extracted at certain time intervals, and the TOC concentration of new organic pollutants in the system was detected using a TOC analyzer.

[0078] Figure 6 The figure is a diagram showing the mineralization effect of the electrode material of Example 1 on different new organic pollutants in the electro-Fenton system. Figure 6 As shown, the 2wt.% POSS / ACF cathode prepared in Example 1 exhibits good mineralization effect on new organic pollutants with different structures. This result shows that the POSS / ACF cathode prepared in the present invention has universal applicability in the degradation of new organic pollutants and has high practical application value.

[0079] The above results indicate that the hydrophobic composite cathode material prepared by modifying the octavinyl-POSS derivative on the surface of activated carbon fiber is a kind of material that can promote H 2 O 2 Electrosynthesis and Fe 2+ The regenerated bifunctional electro-Fenton cathode material can achieve efficient degradation of new organic pollutants in water bodies and has broad prospects for promotion in the field of electrochemical water treatment.

[0080] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.

Claims

1. A method that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: The specific steps include: (1) ultrasonically cleaning the activated carbon fiber with anhydrous ethanol and deionized water in sequence, and drying it for later use; (2) dissolving octavinyl-POSS in an organic solvent by ultrasonic treatment to prepare an octavinyl-POSS solution; (3) applying the octavinyl-POSS solution obtained in step (2) dropwise onto one side surface of the activated carbon fiber pretreated in step (1), and allowing to stand in a fume hood until the organic solvent evaporates, and then drying in a vacuum drying oven; (4) The material obtained in step (3) is placed in a tube furnace and calcined under N2 atmosphere to obtain an activated carbon fiber composite cathode modified with an octavinyl-POSS derivative, which is recorded as POSS / ACF.

2. A method as claimed in claim 1 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: In step (2), the organic solvent is tetrahydrofuran.

3. A method as claimed in claim 1 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: In step (2), the concentration of octaethylene-POSS in the organic solvent is 1.25-12.5 mg / mL.

4. A method as claimed in claim 3 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: In step (2), the concentration of octaethylene-POSS in the organic solvent is 2.5-3 mg / mL.

5. A method as claimed in claim 1 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: In step (3), the drop coating amount of octaethylene-POSS on one side of the activated carbon fiber is 0.625-6.25 mg / cm 2 The specific surface area of ​​POSS / ACF obtained in step (4) is 880m 2 / g or above.

6. A method as claimed in claim 5 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: In step (3), the drop coating amount of octaethylene-POSS on one side of the activated carbon fiber is 0.625-3.125 mg / cm 2 .

7. A method as claimed in claim 1 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: In step (3), the standing time in the fume hood is 15-60 min; the vacuum drying temperature is 50-80° C., and the vacuum drying time is 2-5 h.

8. A method as claimed in claim 7 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: In the step (3), the standing time in the fume hood is 30 min; and the vacuum drying time is 3 h.

9. A method as claimed in claim 1 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: The calcination conditions in the tubular furnace in step (4) are: heating from room temperature to 200-500°C, then calcining at a constant temperature for 5-60 min, and finally cooling to room temperature; the heating rate is 2-10°C / min.

10. A method as claimed in claim 9 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ A method for preparing a regenerated hydrophobic cathode material, characterized in that: The calcination conditions in the tubular furnace in step (4) are: heating from room temperature to 350° C., then calcining at a constant temperature for 30 min, and finally cooling to room temperature; the heating rate is 5° C. / min.

11. A method according to any one of claims 1 to 10, which can simultaneously promote H2O2 electrosynthesis and Fe 2+ Regenerated hydrophobic cathode material.

12. A method as claimed in claim 11 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ Use of a regenerated hydrophobic cathode material, characterized in that The hydrophobic cathode material is used in electrochemical in-situ electrosynthesis of H2O2 or electro-Fenton degradation of organic pollutants in water.

13. A method as claimed in claim 12 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ Use of a regenerated hydrophobic cathode material, characterized in that The in-situ electrosynthesis of H2O2 application process comprises: using an electrolytic cell without a diaphragm in the middle as a reactor, at room temperature, using a 0.01-0.1 mol / L sodium sulfate aqueous solution as an electrolyte, adjusting the pH of the electrolyte to 2-4, using the hydrophobic cathode material as the system cathode, using a platinum electrode as the system anode, and continuously stirring the electrolyte at a speed of 1000-3000 r / min to prepare hydrogen peroxide; the cathode and the anode are externally connected to a DC power supply, and the cathode is applied with a potential of 5-40 V.

14. A method as claimed in claim 12 that can simultaneously promote H2O2 electrosynthesis and Fe 2+ Use of a regenerated hydrophobic cathode material, characterized in that The application process of degrading organic pollutants in water comprises: using an electrolytic cell without a diaphragm in the middle as a reactor, at room temperature, using an aqueous solution containing 0.01-0.1 mol / L sodium sulfate, 0.1-1 mM ferrous sulfate and 10-50 mg / L organic pollutants as an electrolyte, adjusting the pH of the electrolyte to 2-4, using the hydrophobic cathode material as a cathode and a platinum sheet as an anode to construct the homogeneous electro-Fenton system, continuously stirring the electrolyte at a speed of 1000-3000 r / min to degrade the organic pollutants; the cathode and the anode are externally connected to a DC power supply, and the potential applied to the cathode is 5-40 V; the organic pollutant is one of bisphenol A, carbamazepine, and chloroquine.

Citation Information

Patent Citations

  • Method for changing oxygen reduction activity of cathode by regulating and controlling hydrophilicity and hydrophobicity

    CN110565112A

  • Halogen-free flame-retardant PPO / HIPS composite material and preparation process thereof

    CN114479420A